2022
DOI: 10.1007/s42114-022-00542-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(butanediol sebacate-butanediol) terephthalate (PBSeT) reinforced by hydrogen bond containing amide group, with good mechanical properties and improved water vapor barrier

Abstract: Hydrogen-bonded PBSeT copolyesters are synthesized by introducing a polar amide unit into the molecular chain by adding decyldiamine. Two-step esteri cation and one-step polycondensation melt polymerization were adopted. ATR-FTIR and 1HNMR demonstrated the successful introduction of the amide unit. The effect of adding an amide unit on many properties was also discussed. Due to the formation of hydrogen bond, the force of the molecular chain is increased, the crystallinity is increased by 5.91%, and the yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The TGA results revealed that the Ni(OH) 2 located in the zeolite–carbon matrix was comparatively more stable. Similar enhancements in thermal stability have also been achieved by many other authors through hybridization with carbon materials. …”
Section: Resultsmentioning
confidence: 76%
“…The TGA results revealed that the Ni(OH) 2 located in the zeolite–carbon matrix was comparatively more stable. Similar enhancements in thermal stability have also been achieved by many other authors through hybridization with carbon materials. …”
Section: Resultsmentioning
confidence: 76%
“…Thermal gravimetric analysis (TGA) measurements can be launched to analyze the thermal stability and thermal decomposition of polymers. [ 43–46 ] TGA curves of PVBs with different molecular weights are given in Figure 3, which clearly indicates the presence of two main stages in the degradation of the PVBs. The decomposition of PVB‐1799 occurred in the temperature ranges of 280–510°C and 520–620°C, while PVBs with higher molecular weights degraded in the temperature ranges of roughly 250–450°C and 450–650°C.…”
Section: Resultsmentioning
confidence: 94%
“…A weight loss with a broad shoulder between 200 and 800 • C occurs for all the samples and should be ascribed to the removal of silanol groups. 15,20,21,[50][51][52] For the amorphous SiO 2 NPs calcinated at 500 and 600 • C as well as calcinated at 600 and 800 • C and rehydroxylated, the weight loss associated with the silanol groups accounts for 1.0%, .6%, 2.5%, and 1.2%, respectively (Table 2). The amorphous SiO 2 NPs calcinated at 800 • C show almost no significant weight loss associated with the silanol groups.…”
Section: Resultsmentioning
confidence: 99%